The Within-Country Distribution of Brain Drain and Brain Gain Effects: A Case Study on Senegal - Philippe Bocquier; Narcisse Cha'Ngom; Frédéric Docquier; Joël Machado (Institute of Labor Economics (IZA), 2023)
Existing empirical literature provides converging evidence that selective emigration enhances human capital accumulation in the world's poorest countries. However, the within-country distribution of such brain gain effects has received limited attention. Focusing on Senegal, we provide evidence that the brain gain mechanism primarily benefits the wealthiest regions that are internationally connected and have better access to education. Conversely, human capital responses are negligible in regions lacking international connectivity, and even negative in better connected regions with inadequate educational opportunities. These results extend to internal migration, implying that highly vulnerable populations are trapped in the least developed areas.
Keywords: J24; J61; O15; R23; E24; 330; human capital; migration; selection; brain drain; brain gain; Senegal